FRI0399 COLCHICINE IS NOT EFFECTIVE FOR REDUCING OSTEOARTHRITIC HAND PAIN COMPARED TO PLACEBO: A RANDOMISED, PLACEBO-CONTROLLED TRIAL (COLAH). (2nd June 2020) - Davis, C.; Ruediger, C.; Dyer, K.; Lester, S.; Graf, S.; Kroon, F. P. B.; Whittle, S.; Hill, C.
Abstract : Background: Current pharmacotherapies to treat or prevent hand osteoarthritis are limited. Colchicine, an anti-inflammatory agent effective at reducing joint pain and swelling in gouty arthritis, may offer relief in hand osteoarthritis, though this has not been investigated before. 1 Objectives: To investigate the efficacy of colchicine compared to placebo on VAS pain scores over 12 weeks in adults with hand osteoarthritis in a randomised, double-blind controlled trial. Methods: 64 community-dwelling adults with hand osteoarthritis (American College of Rheumatology criteria) 2 (54 females, 48-79 years) were randomised 1:1 to colchicine (0.5mg twice daily) or placebo for 12 weeks. VAS pain scores (worst affected hand) were obtained at baseline and weeks 6, 12, and after treatment withdrawal at week 16. Secondary outcome measures included grip strength, C-reactive protein (CRP) and tender and swollen joint count (TSJC). Grip strength, TSJC and CRP were obtained at baseline and week 12. Intention-to-treat analyses, adjusted for age and gender, were performed using constrained longitudinal data analysis models in Stata v16. 3 This study is registered with the Australia New Zealand Clinical Trials Registry, ACTRN12617001524381. Results: 58 participants completed the study (N=27 colchicine, N=31 placebo, withdrawal rate 9%). Mean (S.D) VAS score of the affected hand at baseline was 71.4 (14.5) mm in the placebo and 65.4 (15.0) mm in the colchicine group (p = 0.11). VAS scores improved during treatment, but were comparable between groups at week 6, 12 and 16 (Table 1 ). There were no differences between groups at week 12 for CRP, TSJC or grip strength (Table 1 ). Adverse events related to study medications included nausea (n=4), diarrhoea (n=9), vomiting (n=3), bloating (n=1) and reflux (n=1). Conclusion: Colchicine 1mg daily for 12 weeks was not effective in improving pain, tender and swollen joint count or grip strength in symptomatic hand osteoarthritis patients. This study does not support colchicine for treatment of symptoms of hand osteoarthritis. References: [1]Leung, YY, Hui, LLY, Kraus, VB 2015. Colchicine-Update on mechanisms of action and therapeutic uses. Seminars in Arthritis and Rheumatism ; 45: 341-350. [2]Altman, R, Alarcon, G, Appelrouth, D et al, 1990. American College of Rheumatology criteria for the classification and reporting of osteoarthritis of the hand. Arthritis Rheumatology; 33(11): 1601-10. [3]Liu GF, Lu K, Mogg R, et al. 2009. Should baseline be a covariate or dependent variable in analyses of change from baseline in clinical trials? Stat Med ; 28: 2509–30. Characters from table content including title and footnotes: 465 Disclosure of Interests: None declared